Effect of Diesel Exhaust Particles on House Dust Mite-Induced Airway Eosinophilic Inflammation and Remodeling in Mice - Go Takahashi; Hiroyuki Tanaka; Keiko Wakahara; Reishi Nasu; Mikiko Hashimoto; Kosuke Miyoshi; Hirohisa Takano; Hirotaka Yamashita; Naoki Inagaki; Hiroichi Nagai (Elsevier, 2010)
Recent research has focused on the effects of ambient particulate pollution and much evidence has indicated that particulate pollution is associated with the onset of asthma and allergy; however, the effect of diesel exhaust particles (DEP) on the development of allergen-induced airway remodeling has not been fully investigated in vivo. In the present study, we examined the effects of DEP on Dermatophagoides farinae allergens (Der f)-induced asthma-like phenotypes in mice. Mice were administered i.t. 8 times with Der f. DEP were injected i.t. with Der f 4 times throughout the experiment or twice at the sensitization period. In both cases, DEP aggravated Der f-induced increases in airway responsiveness to acetylcholine, the number of eosinophils and neutrophils in the bronchoalveolar lavage fluid (BALF), serum Der f-specific IgG1 levels, Th2 cytokines and transforming growth factor-β 1 levels in BALF, and amount of hydroxyproline in the right lungs. Furthermore, goblet cell hyperplasia and subepithelial fibrosis were also markedly aggravated. These findings indicate that DEP can potentiate airway remodeling induced by repeated allergen challenge as well as Th2-drived airway hyperresponsiveness, eosinophilic inflammation, and IgG1 production and that DEP can exhibit adjuvant activity for airway remodeling, probably due to the enhancement of allergen sensitization and/or of Th2 polarizing pathways. Keywords:: bronchial asthma, Dermatophagoides farinae, goblet cell, subepithelial fibrosis, transforming growth factor-β1